Discounting, beyond utilitarianism - Marc Fleurbaey; Stéphane Zuber (Economics: The Open-Access, Open-Assessment E-Journal, 2015)
Discounted utilitarianism and the Ramsey equation prevail in the debate on the discount rate on consumption. The utility discount rate is assumed to be constant and to reflect either the uncertainty about the existence of future generations or a pure preference for the present. The authors question the unique status of discounted utilitarianism and discuss the implications of alternative criteria addressing the key issues of equity in risky situations and variable population. To do so, they introduce a class of intertemporal social objectives, named Expected Prioritarian Equally Distributed Equivalent (EPEDE) criteria. The class is more flexible than discounted utilitarianism in terms of population ethics and it disentangles risk aversion and inequality aversion. The authors show that these social objectives imply interesting modifications of the Ramsey formula, and shed new light on Weitzman's "dismal theorem".
Keywords: D63; 330; discounted utilitarianism; social discounting